Nutrition intervention through stunting education on pregnant and breastfeeding women group - Mukty, Ma'rifat Istiqa; Kusuma, Nina Isywara; Ilyas, Asmiana Saputri; Sulistyaningtyas, Nunik; Daud, Anna Maria; HB, Erlina; Muhammad, Karlyna Bte (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
Stunting is one of the public health problems that is still a concern in Indonesia with a high prevalence at both national and local levels. Based on Riskesdas 2020, the prevalence of stunting in Indonesia reached 27.67%, while the national target is 14% by 2024. To support these efforts, Tri Tunas Nasional Institute of Technology and Health in collaboration with Rumah Zakat organized a community service program entitled "Healthy Mothers, Stunting-Free Children Agent". This activity was aimed at pregnant and breastfeeding mothers in Rapokalling District, Makassar, with the aim of increasing their knowledge and awareness about stunting and how to prevent it. This program uses participatory education methods, interactive discussions, and food distribution as practical support. Evaluation was conducted through pre-test and post-test to measure knowledge improvement. Results showed a significant increase in participants' understanding of stunting and balanced nutrition, as well as behavioral changes towards a healthy diet. These findings demonstrate the importance of community-based interventions integrated with logistical support for successful stunting prevention.